Oil spills - Anderson, Madelyn Klein (New York : F. Watts, 1990)
Describes the problem of oil spills, their effect on the environment, and what must be done to clean up after them.
Includes bibliographical references.
School Library Journal.
Wilson's Children.
Wilson's Junior High School.
5.0
4-6.
Keywords: Oil spills -- Environmental aspects -- Juvenile literature; Pollution -- Juvenile literature; Oil spills -- Environmental aspects; Pollution; Oil spills -- Environmental aspects; Pollution